The Impact of CEFR-Related Professional Learning on Second-Language Teachers’ Classroom Practice: The Case of French in Canada - Rehner, Katherine; Lasan, Ivan; Popovich, Anne; Palta, Zehra (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
This study explores the impact of professional learning about the Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFR) on second language (L2) teachers’ classroom practice. Ninety self-selected French as a second language (FSL) teachers across Canada responded to an online survey about their planning, teaching, and assessment/evaluation practices before versus after their professional learning. The results revealed that the impact of such professional learning is wide-reaching and remarkably consistent across all three areas of practice. The teachers reported that their professional learning spurred them to start presenting language through speech acts and based on students’ needs, to emphasize not only linguistic but sociolinguistic and pragmatic competence as well, and to focus more intently on students’ ability to communicate in the L2. The teachers also reported that they increased the use of authentic materials and developed communicative and action-oriented tasks that simulate real-life situations. The findings suggest that CEFR-related professional learning may be used successfully to inspire L2 teachers to implement CEFR-informed classroom practices.